2018
DOI: 10.4102/aveh.v77i1.417
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer and ganglion cell complex thickness in patients with keratoconus

Abstract: Background: Keratoconus, a corneal ectasia, is associated with corneal thinning and altered optical media. Consequently, assessment of the visual field, optic nerve head and intraocular pressure measurements may be challenging in patients with keratoconus. Few studies have investigated posterior segment variables including the retinal nerve fibre layer (RNFL) and ganglion cell complex (GCC) thickness in patients with keratoconus.Aim: To investigate RNFL and GCC thickness in patients with keratoconus.Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Cuppusamy et al, in a comparative study, investigated the measurements of RNFL and RGCL thickness in KCN patients[54]. They found comparable results of these two parameters between KCN and non-Clinically, the induced astigmatism error in KCN patients may act as an artifact while imaging acquisition by OCT. Langenbucher et al demonstrated that high degrees of astigmatism in more advanced cases of KCN might bring changes in peripapillary RNFL findings[57].…”
mentioning
confidence: 99%
“…Cuppusamy et al, in a comparative study, investigated the measurements of RNFL and RGCL thickness in KCN patients[54]. They found comparable results of these two parameters between KCN and non-Clinically, the induced astigmatism error in KCN patients may act as an artifact while imaging acquisition by OCT. Langenbucher et al demonstrated that high degrees of astigmatism in more advanced cases of KCN might bring changes in peripapillary RNFL findings[57].…”
mentioning
confidence: 99%